Antitumour Activities of Selected Pure Compounds Identified from the Serum of Crocodylus porosus, Malayopython reticulatus, Varanus salvator and Cuora kamaroma amboinensis - Jeyamogan, Shareni (2021)
Objectives: Here we determined antitumour effects of purified compounds such as Valdecoxib, Rofecoxib, L-Methionine and Artocarpin against cancer cell lines. Methods: Using purified compounds, assays were performed to determine their effects against cancer cell lines using growth inhibition assays, cytotoxicity assays, and cell survival assays against HeLa, PC3 and MCF7 cells. Results: The results showed that the selected small molecules L-Methionine, Rofecoxib, and Artocarpin suppressed the growth of more than 90% PC3 cells at 40μM. Similarly, Valdecoxib alone and in combination with other molecules exhibited potent growth inhibition and cytotoxicity against cancer cells tested. Peptide from the serum of M. reticulatus, demonstrated selective cytotoxicity against cancer cells without inhibiting the growth of normal cells. Conclusion: These findings are significant and provide a basis for the rational development of therapeutic anticancer agents, however intensive research is needed to determine in vivo effects of the identified molecules together with their mode of action to realize these expectations.